Strengthening The Village Economy In Digital Era Through The Proud Made In Indonesia National Movement - Hermawan, Elpa (International Journal of Educational Research & Social Sciences, 2023)
The purpose of this research is to get the results of strengthening the village economy through the proud national movement made in Indonesia in the digital era. This research uses a qualitative approach with a qualitative descriptive method. The data were taken from the results of observations, documents and forum group discussions at the Proud National Movement meetings held in Indonesia with government stakeholders. Data were analyzed through three stages, including 1) data reduction, namely data sorting according to the needs of research problem analysis, 2) data presentation, namely the process of categorizing data to be analyzed, and 3) conclusion. The results of the study concluded that there was a positive impact on the implementation of the proud national movement program made in Indonesia on strengthening small and medium business actors in villages, especially in the digital era because business actors can carry out production and marketing innovations digitally or penetrate village boundaries so that their products can be known more widely. In addition, business actors have also increased from May 2020 by 8 million to 19.2 million in May 2022 and the target is 30 million by the end of 2023. So, the results of this study provide an understanding that an economic improvement program must be adjusted to technological developments and needs. consumers to get wider market opportunities.